A preliminary study on the utilization of health services among JKN-subsidized beneficiaries in West Tanjung Jabung District - Annisa Putri S; Dwi Noerjoedianto; Lu'ai Hana Adilah (Universitas Gadjah Mada, 2026)
Purpose: Despite the National Health Insurance (JKN) coverage, outpatient service utilization remains suboptimal. In 2023, only 48.20% of the Indonesian population utilized health insurance for primary care. This preliminary study aims to provide an initial exploration of the factors related to health service utilization among subsidized beneficiaries (PBI) at Public Health Centers (Puskesmas) in West Tanjung Jabung District. Methods: This quantitative study employed an analytical cross-sectional survey. The research was conducted at Merlung and Suban Puskesmas. A sample of 106 PBI participants was selected from a population of 26,043 using proportional random sampling. Data were collected using a validated and reliable questionnaire, then analyzed using univariate and bivariate (chi-square) tests. Results: The study found that 62.3% of respondents did not utilize health services in the last month (utilization rate 37.7%). Bivariate analysis revealed that significant factors associated with service utilization were JKN knowledge (p=0.001), employment status (p=0.003), perception of illness (p=0.035), history of chronic disease (p=0.000), and accessibility of information (p=0.041). Conversely, age (p=0.051), education level (p=0.18), and geographical distance (p=0.534) showed no significant correlation. Conclusion: The study identifies several significant factors related to utilization in a bivariate context. As a preliminary finding, these results provide a baseline for future multivariate research to determine the independent predictors of healthcare access among the PBI population.